2003
DOI: 10.1002/syn.10275
|View full text |Cite
|
Sign up to set email alerts
|

Activation of metabotropic glutamate receptor 5 is associated with effect of amphetamine on brain neurons

Abstract: The role of metabotropic glutamate receptor 5 (mGluR5) was explored in mechanisms underlying the action of amphetamine (AMPH). The activity of mGluR5 was monitored by measuring the level of [3H]inositol monophosphates in brain neurons, in response to stimulation of 2-choloro-5-hydroxyphenylglycine (CHPG), a selective agonist of mGluR5. Treatment with 1 microM of AMPH for 1 h or 7 days increased the CHPG (1 mM, 30 min)-evoked phosphoinositide turnover by 46% or 92% and 26% or 84% in cultured cortical and hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…More generally, group I mGluRs seem to be involved in the mediation of long-term neuroadaptations that occur after repeated cocaine (Ghasemzadeh et al 1999;Swanson et al 2001) and amphetamine administration Yu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, group I mGluRs seem to be involved in the mediation of long-term neuroadaptations that occur after repeated cocaine (Ghasemzadeh et al 1999;Swanson et al 2001) and amphetamine administration Yu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase in PME concentrations was seen following d ‐amphetamine administration (58). This is interesting as both human and animal studies have suggested that d ‐amphetamine administration can increase PI‐cycle activity (63–65).…”
Section: Inositol‐depletion Hypothesismentioning
confidence: 99%
“…Previous studies have confirmed that dextroamphetamine administration acts indirectly to stimulate the PI-cycle (Yu et al, 2003, Silverstone et al, 2002Barkai, 1981). Thus, some of the decrease in brain activation following dextroamphetamine may be mediated via the PI-cycle.…”
Section: Discussionmentioning
confidence: 83%
“…There is also evidence that dextroamphetamine stimulates the PIcycle (Yu et al, 2003;Silverstone et al, 2002;Barkai, 1981) and this may conceivably be the mechanism responsible for its effects on brain activation. There is also good evidence that both lithium and valproate can attenuate the PI-cycle, probably acting via different mechanisms (Gurvich and Klein, 2002).…”
Section: Introductionmentioning
confidence: 96%